Distinct Effects of Executive Functioning, Impulsivity and Anxiety on Global and Local Reading Comprehension - Leshem, Rotem; Altman, Carmit (Frontiers in Education, 2021)
Reading comprehension (RC) is a cognitive ability linked with higher-order cognitive functions referred to as executive functions (EFs) and is also associated with educational achievement. To date, there is little research exploring links between reading comprehension, EFs, and personality traits. This study attempts to fill this gap by elucidating the role of EFs, trait impulsivity, and trait anxiety in RC among university students. To achieve a more in-depth examination, RC is divided into its global and local subskills. Ninety university students (83% female) completed self-report questionnaires on EFs, impulsivity, and anxiety, a neuropsychological task for cognitive flexibility, and global/local RC assessments. Our results indicated distinct associations between poor general EFs and poor global RC, poor cognitive flexibility and poor local RC, and, finally, between high impulsivity and adequate global RC. Individual differences in global and local information processing strategies in the context of attentional processes and personal traits of the university students, is discussed.